Socialization of the Sumber Sejahtera Credit Union Cooperative in Ds. Sumber Rahayu, Wanaraya District, Barito Kuala Regency September 25, 2024 - Isra Ul Huda; Ernawati Ernawati; Anthonius Junianto Karsudjono (Penerbit Mandalika Indonesia, 2025)
This report presents the results of the Community Service program on the Socialization of the Credit Union Sumber Sejahtera, conducted in Sumber Rahayu Village, Wanaraya District, Barito Kuala Regency, on September 25, 2024. The event aimed to raise public awareness about the benefits of cooperatives, particularly in the areas of savings and loans, as well as the role of cooperatives in financial inclusion. Through this socialization, it is expected that the community will gain a deeper understanding of the services provided by the cooperative and the importance of sustainable cooperative management for local economic development. The socialization also focused on enhancing financial literacy among cooperative members and local residents. This study highlights the importance of cooperative involvement in strengthening rural economies and promoting inclusive and sustainable economic growth. The outcomes of this community service are expected to strengthen the relationship between the cooperative and the community, while also increasing participation and understanding of the significance of cooperatives in the local economy.